Ambiente educativo en una facultad de medicina peruana: una tendencia negativa a lo largo de los años académicos - Flores-Flores, Oscar (2018)
Background: Educational environment refers to the material resources and interpersonal relationships of an educational institution. Aim: To describe the educational environment of a Peruvian medical school and to explore a possible association between curricular years and the educational environment. Material and Methods: A cross-sectional study was conducted using the Dundee Ready Education Environment Measure (DREEM) to evaluate the educational environment of a Peruvian medical school. Data collection consisted in online surveys completed voluntarily by 1st through 6th year medical students between April and October 2015. Results: The questionnaire was completed by 828 of 2,421 (34.2%) students. The mean DREEM score was 117 ± 25.6 of a maximum of 200. A poorer perception of the educational environment was associated with later years in the curriculum, when analysis was adjusted for gender, age and academic status (p < 0.001). Conclusions: The educational environment of this medical school scored positively (> 100 points). However, it was evident that medical students in later curricular years had a more negative perception of the educational environment compared to those in earlier academic years.